(untitled) (Bioresearch Communications, 2021)
Introduction: Immunohistochemistry (IHC) is essential in the diagnostic workup of Diffuse Large B cell lymphoma (DLBCL). Determination of biological heterogenicity of Diffuse Large B-cell Lymphoma (DLBCL) is critical to institute precise treatment and predict prognosis. IHC confirms B cell phenotypes, reflects molecular subtype based on cell of origin and determines other immunophenotypic characteristics. Methods and Material: All cases of DLBCL diagnosed in 2020 (Jan-Dec) in histopathology department of Evercare Hospital Dhaka were included in this study. Histopathological sections were stained with CD20, CD3, CD5, CD30, BCL2, BCL6, CD10, MUM1, MYC, Ki67 and other markers. Hans algorithm was applied to classify DLBCL cases into germinal center B-cell (GCB) or Non-GCB. Results: Out of 64 DLBCL cases, 21 (24%) of DLBCL were GCB, while 76% (43 cases) were non-GCB subtypes. 30% cases of DLBCL showed double expression for MYC and BCL2. Fewer cases were immunoreactive for CD5 and CD30. Conclusion: This first study at Dhaka with wide range of antibody to characterize the Immunophenotypic features of DLBCL. The main finding of this study is the identification of non-germinal center B-cell (non-GCB) as the major immunophenotype of DLBCL. This may be an enabler for further studies to observe the clinical outcome of different subtypes of GCB and Non-GCB. Bioresearch Commu. 8(1): 1049-1052, 2022 (January)